Peran Perusahaan terhadap Kesejahteraan Tenaga Kerja di Cv Rizki Mandiri Farm - Logis Gojali, Elga; Falahudin, Aaf; Adam Yuliandri, Lili (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
Welfare is an aspect that is quite important for maintaining and fostering social and economic stability and the fulfillment of all needs, both goods and services. The aim of this research is to analyze the role of CV Rizki Mandiri Farm in improving workforce welfare and to analyze the level of workforce welfare. This research method took one respondent from the manager, one financial person and thirteen employees. From this number, data collection techniques were carried out using survey methods. The analysis technique in this research uses a qualitative and quantitative approach using a Likert Scale. The research results obtained that the overall average value of the variable role of CV Rizki Mandiri Farm in improving the welfare of workers was obtained with a value of 2.39, in the High category. Likewise, the overall average value of the worker welfare level variable at CV Rizki Mandiri Farm is 2.53, in the High category. Thus, it can be concluded that CV Rizki Mandiri Farm has carried out its role in improving workforce welfare in accordance with applicable standards.